2018
DOI: 10.1101/329409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Positive memory specificity reduces adolescent vulnerability to depression

Abstract: Depression is the leading cause of ill health and disability worldwide1. A known risk factor of depression is exposure to early life stress2. Such early stress exposure has been proposed to sensitise the maturing psychophysiological stress system to later life stress3. Activating positive memories dampens acute stress responses with resultant lower cortisol response and improved mood in humans4 and reduced depression-like behaviour in mice5. It is unknown whether recalling positive memories similarly reduces a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…With regards to the activation of positive memories, some studies have identified that positive memories dampen both the cortisol response in experimental stressful situation and morning cortisol level in adolescents exposed to early life stress (Speer and Delgado, 2017). In addition, positive memories have been associated with lower negative affect and self-cognition (Askelund et al, 2019). Furthermore, the experimental activation of positive memories was found to be associated with greater activity in brain regions previously related to the regulation of emotions, such as the bilateral ventrolateral prefrontal cortex (VLPFC) and corticostriatal regions associated with reward-processing (Speer and Delgado, 2017).…”
Section: The Neuroscience Of Self-efficacy Humor and Positive Emotionsmentioning
confidence: 99%
“…With regards to the activation of positive memories, some studies have identified that positive memories dampen both the cortisol response in experimental stressful situation and morning cortisol level in adolescents exposed to early life stress (Speer and Delgado, 2017). In addition, positive memories have been associated with lower negative affect and self-cognition (Askelund et al, 2019). Furthermore, the experimental activation of positive memories was found to be associated with greater activity in brain regions previously related to the regulation of emotions, such as the bilateral ventrolateral prefrontal cortex (VLPFC) and corticostriatal regions associated with reward-processing (Speer and Delgado, 2017).…”
Section: The Neuroscience Of Self-efficacy Humor and Positive Emotionsmentioning
confidence: 99%
“…Importantly, research indicates beneficial effects of retrieving positive memories, such as greater positive affect and decreased negative affect (e.g., Joormann et al, 2007) and reduced post-trauma maladaptive cognitions (Askelund et al, 2019). Actually, this subsequently improved affect has other downstream consequences; positive emotions have an adaptive function and relate to several aspects of well-being, such as life satisfaction or adaptive responses to negative events (Waugh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, reduced memory specificity may have detrimental long-term effects including greater post-trauma severity (Hermans et al, 2004) and delayed post-trauma recovery Ehlers & Clark, 2000) by preventing the contextualization and integration of trauma memories with existing beliefs (Resick & Schnicke, 1993) and other memories (Conway & Pleydell-Pearce, 2000;Ehlers & Clark, 2000). Indeed, research indicates that greater positive memory specificity facilitates adaptive coping to stressors (Askelund et al, 2019). Alternatively, lower post-trauma symptom severity may relate to improved working memory and cognitive functioning, which in turn may improve positive memory retrieval (Barrett et al, 1996;Dalgleish et al, 2007;.…”
Section: Summary Of Findings and Implicationsmentioning
confidence: 99%